1995
DOI: 10.1007/bf00192885
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis: mechanistic insights, neovascular diseases, and therapeutic prospects

Abstract: This review of angiogenesis aims to describe (a) stimuli that either elicit or antagonize angiogenesis, (b) the response of the vasculature to angiogenic or anti-angiogenic stimuli, i.e., processes required for the formation of new vessels, (c) aspects of angiogenesis relating to tissue remodeling and disease, and (d) the potential of angiogenic or antiangiogenic therapeutic measures. Angiogenesis, the formation of new vessels from existing microvessels, is important in embryogenesis, wound healing, diabetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
284
0
14

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(301 citation statements)
references
References 148 publications
2
284
0
14
Order By: Relevance
“…Cells were permitted to migrate into the area of clearing for 24 h. Immediate after wounding and at the end of the experiment (after 24 h), wounds were photographed and semiquantitative measurements were taken of control and treated wounds. A mean wound width was determined, and the average percent wound closure was calculated as described previously (13).…”
Section: Confocal Microscopy Analysis Of Rhoa and Actin Filamentsmentioning
confidence: 99%
“…Cells were permitted to migrate into the area of clearing for 24 h. Immediate after wounding and at the end of the experiment (after 24 h), wounds were photographed and semiquantitative measurements were taken of control and treated wounds. A mean wound width was determined, and the average percent wound closure was calculated as described previously (13).…”
Section: Confocal Microscopy Analysis Of Rhoa and Actin Filamentsmentioning
confidence: 99%
“…These are all growth factors with reported efficacy in stimulation of vascularization 28. Subsequently, liposomes were designed for delivery of the selected growth factor in the PDLLCL scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] Following receptor binding, endothelial cells are stimulated to proliferate and form tube-like structures, the first steps in forming new blood vessels, a process known as angiogenesis. 37,38 Preclinical studies have demonstrated that delivery of the VEGF gene into ischemic tissue can stimulate the development of collateral arteries in animal models of peripheral and myocardial ischemia. [39][40][41][42] Adenovirus-mediated gene delivery has the ability to deliver high concentrations of proteins such as VEGF to a localized area within ischemic tissue, while minimizing the risks associated with systemic administration of angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%